Vapor phase dealloying kinetics of MnZn alloys. (15th June 2021) - Lu, Zhen; Zhang, Fan; Wei, Daixiu; Han, Jiuhui; Xia, Yanjie; Jiang, Jing; Zhong, Mingwang; Hirata, Akihiko; Watanabe, Kentaro; Karma, Alain; Erlebacher, Jonah; Chen, Mingwei
Abstract: Vapor phase dealloying (VPD) is an environmentally-friendly method for fabricating nanoporous materials by utilizing the saturated vapor pressure difference of elements to selectively drive sublimation of one or more components from an alloy. VPD kinetics has not been explored and rate-controlling factors of the solid-gas transformation within complex nanostructure remain unknown. Using manganese-zinc alloys as a prototype system, we systematically investigated the dependence of dealloying velocity on temperature and pressure and presented a model to quantitatively describe the dealloying kinetics. We found that the dealloying velocity exhibits a linear to power law transition at a critical dealloying depth, resulting from the interplay between the kinetic process of dealloying and dealloyed microstructure. This transition bridges ballistic evaporation at early time to Knudsen diffusion of Zn vapor in developed pore channels where the Zn partial pressure at the dealloying front reaches the local equilibrium between the solid and vapor phases. By comparing activation energies for VPD and bulk zinc sublimation, the entire energy landscape of VPD is measured. The fundamental understanding of VPD kinetics paves an effective way to design dealloyable precursor alloys and to optimize dealloyed microstructure of VPD materials for a wide range of applications. Graphical abstract: Image, graphical abstract